2006
DOI: 10.1016/j.jnoncrysol.2006.01.096
|View full text |Cite
|
Sign up to set email alerts
|

Photoprogrammable molecular hybrid materials for write-as-needed optical devices

Abstract: The application of photosensitive materials to provide immediately configurable optical device functionality in integrated photonic systems has motivated an examination of the unique materials requirements associated with this alternative operational mode. In this case, a reliable photoinduced index change is needed when photopatterning under non-laboratory conditions utilizing compact, integrable optical sources. Molecular hybrid thin films, based on inorganic, Group IVA linear-chain polymers, are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The researchers observed that laser treatment induced chain ordering and porosity onto the PDMS surface, which resulted in a super-hydrophobic surface using a 248-nm KrF laser and a 266-nm laser. Other researchers introduced UV photosensitivity in PDMS using ultraviolet (UV) radiation, causing a bleaching reaction that severely degrades the material properties . Our approach is to obtain highly tunable integrated optical devices by enhancing the fs photoinscription response of the material without damaging the material properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers observed that laser treatment induced chain ordering and porosity onto the PDMS surface, which resulted in a super-hydrophobic surface using a 248-nm KrF laser and a 266-nm laser. Other researchers introduced UV photosensitivity in PDMS using ultraviolet (UV) radiation, causing a bleaching reaction that severely degrades the material properties . Our approach is to obtain highly tunable integrated optical devices by enhancing the fs photoinscription response of the material without damaging the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers introduced UV photosensitivity in PDMS using ultraviolet (UV) radiation, causing a bleaching reaction that severely degrades the material properties. 20 Our approach is to obtain highly tunable integrated optical devices by enhancing the fs photoinscription response of the material without damaging the material properties. It has been demonstrated that PDMS can be laser-structured using direct writing with appropriate photoinitiators 21 , 22 and thermoinitiators.…”
Section: Introductionmentioning
confidence: 99%
“…It can undergo a strain of 40% in the linear elastic regime and up to 170% before failure for bulk samples 7 . Laser writing on PDMS has been previously demonstrated using UV light 8 . A refractive index (RI) change (Δn) of ~ 0.14 has been reported but bleaching reaction of the PDMS was also observed resulting in degradation of the polymers chains which affects the mechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%